Pengendalian Inflasi di Indonesia Berbasis Kebijakan Fiskal dengan Model seemingly Unrelated Regression - Lia Nazliana Nasution; Ade Novalina (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2020)
This study aims to see how effectively fiscal policy can control inflation in Indonesia. The fiscal policy variables used are tax revenue, government expenditure, and foreign direct investment (FDI). The data used are secondary data types ranging from 1982 to 2018. Based on the results of research using the Seemingly Unrelated Regression (SUR) method, shows that fiscal policy variables measured through tax revenues, FDI, and government spending, have a significant effect on the development of Indonesia's inflation. Tax revenue has a substantial impact on government spending. Likewise, FDI has a significant impact on the money supply in Indonesia during the observation.